Molecular characterization and expression pattern of tobacco (Nicotiana tabacum) ascorbate oxidase gene. Issue 6 (1st November 2016) - Li, Zhihua; Chen, Jian; Wang, Chao; Huang, Yunjie; Wang, Jiajun; Dong, Shifei; Tang, Lu; Liu, Jiani; Chen, Zebin; Wang, Dingkang; Xu, Shengguang; Yu, Lei
ABSTRACT: The complete coding sequence of one tobacco ( Nicotiana tabacum ) gene, ascorbate oxidase (AO), was isolated by the application of reverse transcription-polymerase chain reaction. The tobacco AO gene consists of a 1722-bp open reading frame and encodes a protein of 573 amino acids. Sequence comparison analysis revealed that the tobacco AO protein shares high homology with the AO proteins of Lycopersicon esculentum (89%), Populus trichocarpa (75%), soybean (74%), castor bean (73%) and peach (73%). The prediction of transmembrane helices showed that tobacco AO might be a transmembrane protein. The expression profile was studied and the results indicated that the tobacco AO gene was diversely expressed in different tobacco tissues, including leaves, stem, roots and flowers. Our experiment laid the grounds for further research on this tobacco gene.